National innovation system as a component knowledge economy: problems and prospects - Золотых, Ирина Борисовна (Technology audit and production reserves, 2015)
As a result of conducted research the following work has been done: - the theoretical and methodological base of the national innovation system has been grounded, mainly the meaning of the modern concepts of "national innovation system", "information infrastructure" and "information and communication technologies" has been determined; - the interaction of the national innovation system and information and communication technologies (ICT) has been shown; - the problems of creation of information infrastructure functioning mechanism in Ukraine have been determined; -the experience of information infrastructure development in the USA as a leading country in that field has been studied. The research on the given problem is caused by the necessity of forming the knowledge economy in Ukraine, as that type of economy is capable of bringing it to an advanced level based on the scientific and technological progress providing the competitiveness of the Ukrainian products on the world market. As a result of research it has been stated that the effectiveness of the innovation development in Ukraine is rather low. To solve the mentioned problems it is necessary to study and use the experience of the countries that have successfully solved the tasks of innovation development of their national economy.